Energy Resources Management Enabled by Internet of Things Devices - Gomes, Luis (2021)
The participation of small end-users in the smart grid brings benefits for the end-users and for the smart grid. This paper will treat end-users using communities involving energy sharing between private buildings (residential and commercial) and public buildings. The energy can be shared among end-users and the community can be managed centralized. The paper uses IoT devices to enable the active participation of end-users. The use of this type of devices is growing and more and more market available product are appearing. The remote control and monitor capabilities, provided by the normality of IoT devices, can and should be used in energy management systems as enablers. This paper uses IoT devices, located in end-users, to enable the participation of these player in the community. The paper will propose a smart energy community platform and show its results.